Intrathecal Baclofen in Spinal Spasticity: Frequency and Severity of Withdrawal Syndrome - Štětkářová, Ivana; Brabec, Karel; Vaško, Peter; Mencl, Libor (Pain physician, 2015)
BACKGROUND: Intrathecal baclofen (ITB) delivered by programmable pump devices represents an important modality for long-term treatment of severe spinal spasticity. OBJECTIVE: One of the serious adverse events is a withdrawal syndrome after sudden interruption of ITB delivery. In this study, we analyzed the frequency and severity of this complication. Treatment recommendations follow. STUDY DESIGN: Case study. SETTING: Academic medical center. METHODS: A total of 54 ITB pumps were successfully implanted in 39 patients with severe intractable spasticity (24 with spinal cord injury, 15 with multiple sclerosis, 24 men, age range 21-59 years). RESULTS: Eight patients developed a withdrawal syndrome on total a daily dose of ITB between 90-420 μg/day. Seven patients had catheter-related complications. In one patient, pump failure was observed due to its corrosion. Within the group, baclofen withdrawal syndrome occurred once in 20.1 pump-years counted out of 160.4 pump-years of ITB treatment. LIMITATIONS: Small sample size. CONCLUSIONS: ITB withdrawal syndrome is a rare but life-threatening event and prompt diagnosis before treatment initiation is critical. The reported events were mostly mild due to the acute treatment regime and probably due to a lower dose of ITB. A prerequisite for successful ITB treatment is a deep knowledge of complications and their prompt management in the hands of a multidisciplinary team in specialized centers.
Keywords: implantabilní infuzní pumpy; Adolescent; katétry; Muscle Relaxants, Central; baklofen; Infusion Pumps, Implantable; Multiple Sclerosis; lidé středního věku; centrálně působící myorelaxancia; Equipment Failure; abstinenční syndrom; lidé; Adult; Injections, Spinal; Middle Aged; dospělí; poranění míchy; Baclofen; nemoci páteře; Muscle Spasticity; svalová spasticita; Catheters; Male; spinální injekce; roztroušená skleróza; mladý dospělý; Humans; mužské pohlaví; Young Adult; selhání zařízení; Spinal Diseases; Spinal Cord Injuries; Substance Withdrawal Syndrome; mladiství